Good practices for designing and experimental testing of dynamically excited jointed structures: The Orion beam - Teloli, Rafael de O. [UNESP]; Butaud, Pauline; Chevallier, Gael; Silva, Samuel da [UNESP] (Elsevier B.V., 2021)
This paper proposes a new lap-joint configuration, the so-called Orion beam. The new setup is composed of two thin beams connected by three bolted joints with contact patches on each connecting bolt. The Orion beam suggests an assembly configuration, in which there are bolts dedicated to static functions to guarantee structural integrity and those that perform damping functions to increase energy dissipation due to frictional contact. In particular, this paper analyzes the influence of the Orion beam's design in the repeatability of experimental measurements and the impact of the tightening torque and excitation amplitudes on the system's response. A feedback controller is proposed to control the excitation amplitudes during step-sine tests in the vicinity of resonance frequencies to measure the frequency response curves used to perform such analysis. Additionally, a single-degree-of-freedom Duffing-Van der Pol oscillator is proposed to evaluate, through its calibrated parameters, the impact of several tightening torque conditions and multiple excitation amplitudes on the structural stiffness and damping considering the vibration mode that promotes pronounced deformation around the lap-joint. Due to the presence of contact patches, the results show that the structure maintained impressive repeatability after several experimental measurements. Besides, it is possible to increase the damping for amplitude attenuation without significant losses in the contact stiffness.
Keywords: Lap-joint; Tightening torque; Experimental practices; Nonlinear dynamics; Contact mechanics; Friction damping